2022
DOI: 10.1177/10225536221127668
|View full text |Cite
|
Sign up to set email alerts
|

Swelling assessment after total knee arthroplasty

Abstract: Background Total knee arthroplasty is a commonly performed elective orthopaedic surgery. Patients may endure substantial knee swelling following surgery, which are attributable to both effusion and edema. Studies have been aiming to identify an accurate and reliable method to quantify post-operative knee swelling to aid monitoring progress and treatment. The aim of this article was to review the means of clinically applicable measurements for knee swelling post TKA. Methods The medical literature was searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…4,5 In addition, postoperative lower limb swelling following TKA are one of the other important causes of dissatisfaction, and contribute to pain, inflammation, reduced range of motion, functional limitation and negative perception of enhanced recovery. [6][7][8][9][10] It is reported that the incidence of significant joint swelling after TKA is close to 20%. 8 Enhanced recovery after surgery (ERAS) has been introduced to arthroplasty in recent years and aims to reduce patients' stress response and postoperative complications, alleviate patients' pain, and shorten the length of hospital stays in TKA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In addition, postoperative lower limb swelling following TKA are one of the other important causes of dissatisfaction, and contribute to pain, inflammation, reduced range of motion, functional limitation and negative perception of enhanced recovery. [6][7][8][9][10] It is reported that the incidence of significant joint swelling after TKA is close to 20%. 8 Enhanced recovery after surgery (ERAS) has been introduced to arthroplasty in recent years and aims to reduce patients' stress response and postoperative complications, alleviate patients' pain, and shorten the length of hospital stays in TKA.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] It is reported that the incidence of significant joint swelling after TKA is close to 20%. 8 Enhanced recovery after surgery (ERAS) has been introduced to arthroplasty in recent years and aims to reduce patients' stress response and postoperative complications, alleviate patients' pain, and shorten the length of hospital stays in TKA. 11,12 Dexamethasone, a corticosteroid with powerful anti-inflammatory and antiemetic effects, has been frequently used in enhanced recovery protocol of TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, such imaging techniques have been reported in the literature. Yau et al 38 argued that MRI is the most accurate noninvasive method for detecting knee effusion after TKA. However, the authors noted that MRI is typically reserved for assessing complications such as infection, joint loosening, wear, and malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced recovery after surgery pathway has emerged as one of the best strategies to improve the value and quality of surgical care 4,5 . Efforts to enhance recovery after TKA have identified postoperative lower-extremity swelling as one of the most frequent causes of patient dissatisfaction and pain, and such pain after surgery has been linked to inflammation, reduced range of motion, and the inhibition of quadricep function [6][7][8][9][10] . It has been reported that up to 20% of patients experience severe joint swelling following TKA 8 .…”
mentioning
confidence: 99%
“…Qiuru Wang, MD 1 Qunhua Jin, MD 2 Lijun Cai, MM 1 Chengcheng Zhao, MM 1 Pengfei Feng, MD 2 Jie Jia, MD 3 Weihua Xu, MD 3 Qirong Qian, MD 4 Zheru Ding, MD 4 Jianzhong Xu, MD 5 Chenxi Gu, MD 5 Shoutao Zhang, MD 6 Hui Shi, MD 6 Hongbing Ma, MD 7 Ye Deng, MD 7 Tingjiu Zhang, MD 8 Yuan Song, MD 8 Qiang Wang, MD 9 Yinchang Zhang, MD 9 Xinshe Zhou, MD 10 Lijia Pei, MD 10 Yunkang Yang, MD 11 Jie Liang, MD 11 Tao Jiang, MD 12 Hao Li, MD 12 Huancai Liu, MD 13 Lizhong Wu, MD 13 Pengde Kang, MD, PHD 1…”
mentioning
confidence: 99%